Annual decline in arterial blood oxygen predicts development of chronic respiratory failure in COPD with mild hypoxaemia: A 6‐year follow‐up study. Issue 3 (19th September 2018) - Uemasu, Kiyoshi; Sato, Susumu; Muro, Shigeo; Sato, Atsuyasu; Tanabe, Naoya; Hasegawa, Koichi; Hamakawa, Yoko; Mizutani, Tatsushi; Fuseya, Yoshinori; Tanimura, Kazuya; Takahashi, Tamaki; Hirai, Toyohiro
ABSTRACT: Background and objective: Chronic respiratory failure (CRF) with hypoxaemia is an important pathophysiology in patients with chronic obstructive pulmonary disease (COPD), and existing mild hypoxaemia may be a sign of future CRF development. However, little is known about the trajectory of partial arterial pressure of oxygen (PaO2 ) decline in patients with COPD. We assessed decline in PaO2 and the impact of short‐term reductions in PaO2 to predict future decline in PaO2 . Methods: A total of 172 outpatients with COPD from a prospective cohort study were enrolled. Pulmonary function tests and arterial blood gas (ABG) analyses were conducted at baseline and 1 year after enrolment and changes in PaO2 (ΔPaO2 ) and other parameters were calculated. Survival and incidence of CRF (as assessed by prescription of long‐term home oxygen therapy) were monitored for 6 years. Results: A total of 164 patients completed the observation period and 101 patients had mild hypoxaemia (PaO2 < 80 Torr) at baseline. No patients with normal PaO2 (≥80 Torr) developed CRF, and 10 patients with mild hypoxaemia developed CRF in 6 years. Baseline airflow limitation and diffusion capacity were significantly associated with development of CRF. Receiver‐operating characteristic curve analysis showed that ΔPaO2 of −3.05 Torr/year is a useful cut‐off value to predict development of CRF in 6 years (hazard ratio (HR): 12.6, 95% CI: 3.48–58.73, P < 0.0001). Conclusion: Patients with COPD and mild hypoxaemia may benefit from repeat ABG after 1 year. Although PaO2 trajectories widely varied, significant annual changes in PaO2 of at least −3.0 Torr/year were predictive of CRF development. Abstract : We conducted serial arterial blood gas measurements in patients with COPD. Follow‐up partial arterial pressure of oxygen (PaO2 ) at 1 year in patients with mild hypoxaemia is clinically helpful since change in PaO2 (ΔPaO2 ) of –3.05 Torr/year predicts patients at risk of developing chronic respiratory failure within 6 years. Watch the video abstract